Synthesis of Triazine‐Based Materials by Functionalization with Alkynes. Issue 21 (23rd April 2015) - Braml, Nicole E.; Stegbauer, Linus; Lotsch, Bettina V.; Schnick, Wolfgang
Abstract In this contribution, we report on novel functionalized triazines, which represent new precursors for C/N/(H) compounds or suitable building blocks for carbon‐based functional networks. Our results provide insights into the structural properties of molecular carbon nitride materials and their design principles. Tris(1‐propynyl)‐1, 3, 5‐triazine (C3N3(C3H3)3) and tris(1‐butynyl)‐1, 3, 5‐triazine (C3N3(C4H5)3) were prepared by substitution reactions of cyanuric chloride (C3N3Cl3) with prop‐1‐yne and but‐1‐yne. The crystal structure of tris(1‐propynyl)‐1, 3, 5‐triazine was solved in the orthorhombic space group Pbcn (Z=4, a=1500.06 (14), b=991.48(10), c=754.42(6) pm, V=1122.03(18)×106 pm3), whereas tris(1‐butynyl)‐1, 3, 5‐triazine crystallized in the triclinic space group P−1 (Z=6, a=1068.36(12), b=1208.68(12), c=1599.38(16) pm, α=86.67(3), β=86.890(4), γ=86.890(4)°, V=1997.7(4)×106 pm3). For both structures, planar triazine units and layerlike packing of the molecules were observed. Tris(1‐propynyl)‐1, 3, 5‐triazine is built up from hydrogen‐bonded zig‐zag strands, whereas tris(1‐butynyl)‐1, 3, 5‐triazine shows parallel layered arrangements. Both compounds were investigated by NMR spectroscopy, IR spectroscopy, and differential thermal analysis/thermogravimetric analysis, which provided insights into their structural, chemical, and thermal properties. In addition, tris(1‐propynyl)‐1, 3, 5‐triazine was pyrolyzed and a new polymeric triazine‐based compound containing mesitylene units was obtained. Its structural features and properties are discussed in detail.